IFLINE smernice za predmetno označevanje - Šauperl, Alenka (Knjižnica, 2005)
IFLA Principles Underlying Subject Heading Languages were published in 1995 and translated into Slovene in 2002. They try to recover the theory of indexing languages from an analysis of subject heading languages that are used in libraries around the world. These guidelines are illustrated with examples from Splošni slovenski geslovnik (Slovene General Subject Headings, Sears List of Subject Headings, and Library of Congress Subject Headings (LCSH). Studies on the use of LCSH by users of library catalogs were reviewed to determine weaknesses of the IFLA Principles. Changes were suggested, which would make subject retrieval easier for users. The reviewed subject heading languages reflect the needs of traditional librarians and card catalogs. These often conflict with user needs, characteristics of online catalogs and modern librarians. Subject heading languages could be improved if we would take into account the vast knowledge of user behavior and capabilities of information technology. For a better subject access to library materials, we also need to understand the processes of subject analysis and subject description.
Keywords: knjižnični katalogi; knjižnično gradivo; katalogizacija; bibliografski opis; vsebinska obdelava; predmetne oznake; smernice